Improving Protection in Financial Services for Russian Consumers - Rutledge, Sue (World Bank, Washington, DC, 2012)
Over the last decade, consumer credit in the Russian Federation has expanded from almost nothing to 9.2 percent of Gross Domestic Product (GDP) in 2008. This is an average increase of 84 percent a year for five years. Recent developments in financial markets have highlighted the need for consumer protection and financial literacy for the long-term health of the financial sector. The rapid growth of household lending has been accompanied by an increase in the number of households that have difficulty in understanding the risks and obligations that they assume, or the full range of choices available. In the United States mortgage markets for instance, complex financial contracts were sold to borrowers, some of whom had weak credit histories. The consequences were disastrous, and highlight the importance of consumer protection and financial education to prevent other similar events.